Predictors of learning outcomes among students in nutrition science courses at Colorado State University - Peth, James Anthony, author; Melby, Christopher, advisor; Balgopal, Meena, advisor; Foster, Michelle, committee member; Gentile, Christopher, committee member; Hickey, Matthew, committee member (Colorado State University. Libraries, 2018)
Overview This dissertation is a summary of exploratory research to assess predictors of learning outcomes (academic background, conceptions of subject, motivations for studying, and approaches to learning) among students taking two undergraduate nutrition science courses at CSU—Human Nutrition (Course 1) and Integrative Nutrition & Metabolism (Course 2). It was comprised of three studies. Introduction There is a global need for experts trained in nutrition with an integrationist approach to health sciences and equipped to understand complex issues in health and disease. Yet, many students in nutrition sciences courses are not learning at a mastery level and often lack the knowledge and ability to integrate what they have learned to apply it to more advanced courses and their careers. Key factors influencing a student's approach to learning and performance outcomes in a course include their academic background, motivations for learning the subject, conceptions of the subject, and approaches to learning. Pilot data from preliminary research performed during a course re-design project at Colorado State University (CSU) indicate many students begin nutrition science courses with inadequate prior knowledge from prerequisite courses, lack autonomous motivations, exhibit fragmented conceptions of the science of nutrition, and adopt surface, rather than deeper, more meaningful approaches to learning. Methods Exploratory mixed-methods research was performed to assess academic background, motivations for studying nutrition, conceptions of the discipline, and approaches to learning among students in Course 1 (Human Nutrition) and Course 2 (Integrative Nutrition & Metabolism). It was comprised of three studies. The first was an analysis of academic and demographic data for 1,739 students, who had completed Course 1 only (n=1,377) or both Course 1 and Course 2 (n=362) between 2010-2016, to identify and evaluate relationships with in-class exam performance. Studies 2-3 were analyses of semi-structured interviews with students who had completed Course 1 only (n=12) or both Course 1 and Course 2 (n=27) between 2012-2015. Each student reflected on their experiences before and after the course(s) they completed, including their motivations for studying nutrition, conceptions of nutrition as a discipline, and approaches to learning. Transcripts were inductively coded and discrete categories of motivations, conceptions, and approaches were developed using phenomenography. Transcripts were re-analyzed using focused coding, and each student was categorized for each domain. Statistical tests were conducted to evaluate the strength of relationships among academic background variables, motivations, conceptions, approaches, and learning outcomes. Results Pre-course GPA, grades in prerequisite courses, and scores on a prior knowledge test for Course 1 were positively correlated with in-class exam performance. Pre-course GPA was the best predictor for both courses, explaining 51.9% and 43.9% of the score variance in Course 1 and Course 2, respectively. Alone, demographic variables were poor predictors of performance. First-generation status was negatively correlated with performance. Among students interviewed, 100% indicated having an intrinsic interest in learning nutrition before Course 1. However, when taking upper-level nutrition science Courses 1 and 2, 100% suggested being driven to some extent by extrinsic rewards, and only 53.8% and 63% of students suggested having autonomous motivations for studying the specific material covered in Courses 1 and 2, respectively. At the start of Course 1, 87.2% of students had a fragmented conception of nutrition as a discipline; 76.9% adopted a surface approach to learning. Most (82.4%) of the students with a fragmented conception of nutrition science adopted a surface approach to learning. For Course 2, 52% began with a coherent conception of nutrition as a science, and most (81.5%) adopted a deep approach to learning in the course. Statistically significant relationships were identified among motivations, conceptions, and approaches to learning for Course 1. In both Course 1 and 2, coherent conceptions, autonomous motivations, and deep approaches were associated with significantly higher mean grades. Conclusions and Implications Previous academic achievement and prior knowledge provide students a critical foundation for success in upper-level courses in nutrition science. Students develop more coherent conceptions of nutrition as a science, autonomous motivations for learning nutrition, and deep approaches to learning nutrition as they progress through their courses, attempting to meet academic demands. These developmental changes are associated with positive learning outcomes. Efforts should be made to support and increase students' development of cognitive prerequisites, such as prior knowledge from foundational sciences, coherent conceptions of nutrition as a science, and autonomous motivations and deep approaches for learning nutrition earlier in their academic program.